Students' perception of a blended approach in an E-learning environment - Hussain, Hanafizan (2008)
This study of blended approach focused on students' perception when they are encouraged to use it. It identified and described the constituents of the blended approaches that will be delivered according to the combination of technology, theory and practices to teaching and learning in higher education.